Prevalence of ophthalmic abnormalities and refractive changes in Taiwanese children with Down syndrome. - Chia-Ping Chen; Tzu-Hsun Tsai; Yao-Lin Liu; Ni-Chung Lee; Che-Ning Yang; Chao-Wen Lin (PLoS ONE)
Background Ophthalmological manifestations in children with Down syndrome remain significantly underdiagnosed, particularly in Asian populations. This study aimed to investigate the prevalence and characteristics of ophthalmic disorders in Taiwanese children with Down syndrome, analyze their refractive changes over time, and compare findings with existing research across diverse ethnic populations. Methods Comprehensive ophthalmologic examinations were conducted on 148 Taiwanese children with Down syndrome, documenting age, sex, medical history, ocular alignment, visual acuity, and cycloplegic refraction. Annual refractive change assessments were performed using multivariate linear regression analysis for subjects with minimum one-year follow-up. Results Visually significant refractive errors were identified in 75.7% of subjects, with astigmatism being most prevalent (70.3%), followed by hyperopia (31.8%) and myopia (19.6%). Our cohort showed higher astigmatism prevalence compared to previous studies of Asian children with Down syndrome. Longitudinal analysis revealed an annual refractive change of -0.16 ± 0.65 diopters, with age and baseline spherical equivalence emerging as significant contributing factors. Conclusions This study provides unprecedented data on ophthalmic disorders and refractive changes in Taiwanese children with Down syndrome. The high prevalence of refractive errors, particularly astigmatism, underscores the importance of early and regular screening in this population. These findings may inform the development of targeted screening protocols and optimal intervention timing.